The Concept of Human Resource Leadership in Improving the Islamic Characteristics of Students - Andini Habibaturrohmi; Muhammad Jaffar Sodiq; Muhammad Ulya Ilyasa; Miswan Ramdhani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to identify and analyze the role of human resource leadership in enhancing students' Islamic characteristics, motivated by complex challenges in education that demand graduates to be not only academically competent but also possess strong Islamic values. The study aims to analyze HR leadership concepts in Islamic education and their role in shaping students' Islamic characteristics. Using qualitative research methods with a library research approach, this study analyzes primary and secondary data sources through systematic documentation study. Results show that HR leadership plays a strategic role in developing students' Islamic characteristics through Islamic values implementation, professional development, motivation and inspiration, community involvement, moral exemplification, and integration of Islamic values in the curriculum. The implication is that successful formation of students' Islamic character heavily depends on leadership quality in educational institutions.